Visual Representations of Science in a Pandemic: COVID-19 in Images - Delicado, Ana; Rowland, Jussara (Frontiers in Communication, 2021)
This article aims to contribute to the understanding the social dimensions of the 2020 pandemic, with a particular emphasis on the visual practices of science communication in times of health emergency, by analyzing how the COVID-19 pandemic is being represented visually. It seeks to identify the format and content of images used to illustrate online information about the pandemic, in particular in websites of policy institutions, research promoters and media in Portugal and Spain. By examining a sample of 600 images, it aims to identify the messages being conveyed, the effects they intend to provoke and illuminate the differences in representations in these three sources of communication. Differences and similitudes with the visual imaginaries of previous pandemics (influenza, AIDS) are examined. It ascertains that policy websites aim to be mostly prescriptive, relying on infographics to convey prevention and care instructions to its audiences. Science websites rely mostly on stock photos and images from scientific articles to illustrate current research. Media websites are the most diversified in terms of the images they use and the topics they cover. It concludes that representations of science are still very much based on stereotypical imagery of labs and white coats, that representations of the medical side of the pandemic are focused on images of intensive care that aim to generate fear and stimulate responsible behavior and that the social aspects of the pandemic are fairly neglected in most visual representations.